(untitled) - Wise, Christopher (Boulder, 2001)
Presents contemporary literatures of the Sahel, along with contextualizing chapters by critics from Africa, Europe and North America. The text demonstrates the resilienbce and cultural wealth of modern Sahelian society, and provides insights into perspectives on writing, literature and language.
Keywords: African literature,Sahel; History and criticism